Multi-spired Shekhari Shikhara - Temples of India Project Team (Jio Institute, 2024)
Cascading down a central mulashringa (main spire), there are several small miniatures of shikharas (spires), also sometimes called shikharikas, all of which together form the multi-spired shekhari shikhara. At the bottom of the central spine on each elevation can be seen a depiction of Jain deities. The surface of the shikhara aedicules has intricate carvings made up of chaitya (dormers) meshs. Each of the aedicules, both small and large is topped with small ribbed discs which are known as amalakas.